122. All-Cause Mortality Increased With Nontuberculous Mycobacterial Lung Disease in US Medicare. (26th November 2018) - Marras, Theodore; Zhang, Quanwu; Mirsaeidi, Mehdi; Vinnard, Christopher; Hamilton, Keith; Adjemian, Jennifer; Eagle, Gina; Wang, Ping; Zhang, Raymond; Chou, Engels; Winthrop, Kevin L
Abstract: Background: Nontuberculous Mycobacterial Lung Disease (NTMLD) is a chronic, debilitating, and progressive disease. This study evaluates all-cause mortality in patients with NTMLD in the US Medicare. Methods: Patients ( n = 43, 394) were identified from the Medicare database (excluding Part C) based on physician claims for NTMLD on ≥2 separate occasions ≥30 days apart between 2007 and 2015. About 12% patients were <65 years and qualified for Medicare due to disability. A control cohort ( n = 84, 814) was randomly selected and matched to the NTMLD sample by age and sex. The NTMLD diagnosis date was assigned to the matched controls as an index date. Poisson and Cox regression were used to derive descriptive rates and adjusted risk of mortality accounting for baseline comorbidities of pulmonary, immune, cardiovascular, cancer, and other disorders. Results: Mean age was 74 (±10) years and 68% were female in both NTMLD and control cohorts. Mean Charlson comorbidity index (CCI) was 2.9 (standard deviation ±2.6) in NTMLD vs. 1.3 (±1.9) in control cohort. In Medicare members ≥65 years, mean age was 76 (±7) years and 70% were female. Mean CCI was 2.8 (±2.5) in NTMLD cohort vs. 1.4 (±2.0) in control cohort. In Medicare members <65, mean age was 53 (±10) and 49% were female. Mean CCI was 3.8 (±3.3) in NTMLD vs. 1.1 (±1.9) in the control. Observed yearly mortality rates were 9.8% in NTMLD vs. 4.7% in control cohort (rate ratio [RR] = 2.1; 95% CI: 2.03–2.13). In ≥65 Medicare members, the observed rates were 9.7% in NTMLD vs. 5.0% in control cohort (RR = 2.0; 1.9–2.0). In Medicare members <65, the observed rates were 10.4% in NTMLD vs. 2.5% in control cohort (RR = 4.1; 3.8–4.5). Compared with the Asian race, observed mortality was higher in NTMLD patients of Native American (hazard ratio [HR] = 1.69, 1.30–2.19), Black (HR = 1.23; 1.08–1.39), Hispanic (HR = 1.27, 1.07–1.51), or White (HR = 1.18, 1.06–1.31) race (Figure 1). Mortality rates were elevated with NTMLD relative to controls in all age categories from ≥65 years (Figure 2). Adjusted mortality increased with NTMLD by 35% overall (HR = 1.35; 1.3–1.4), by 23% in age group ≥65 (HR = 1.23, 1.19–1.27), and almost doubled in age group <65 (HR = 1.97, 1.80–2.15). Conclusion: Among US Medicare enrollees, NTMLD was associated with a 35% increased risk of mortality overall. Disclosures: T. Marras, Insmed Incorporated: Investigator, Consulting fee and Research grant. Horizon Pharmaceuticals: Consultant, Consulting fee. Red Hill: Consultant, Consulting fee. AstraZeneca: CME, Speaker honorarium. Q. Zhang, Insmed Incorporated: Employee, Salary. G. Eagle, Insmed Incorporated: Employee, Salary. P. Wang, Insmed Incorporated: Employee, Salary. R. Zhang, Insmed Incorporated: Consultant, Consulting fee. E. Chou, Insmed Incorporated: Employee, Salary. K. L. Winthrop, Insmed Incorporated: Consultant and Scientific Advisor, Consulting fee and Research grant.